GDPR: A Game of Snakes and Ladders: How Small Businesses Can Win at the Compliance Game, 1st edition - Alford, Samantha (Routledge, 2020)
For many small businesses, organisations, clubs, artists, faith groups, voluntary organisations/charities and sole traders, applying the General Data Protection Regulation (GDPR) has been like playing a game of "Snakes and Ladders". As soon as you move along the board and climb a ladder, a snake appears, which takes you right back to where you started. Conflicting advice abounds and there is nowhere for these individuals to go for simple answers all in one place. With the threat of fines seeming around every corner, now more than ever is the time for smaller organisations to get to grips with GDPR so that they can demonstrate their compliance.